Employment situation in Latin America and the Caribbean : universal social protection in labour markets with high levels of informality (UN RCLAC SantiagoCL, 2015)
Shows that job performance in the region in 2014 was attibutable both to progress made in labour markets in previous years and to sluggish economic activity over the next twelve months. Puts forward the hypothesis that this performance owes much to previous labour developments that have made many households more resilient. Discusses in detail the challenge surrounding a structural issue standing in the way of further progress in reducing poverty and inequality: how to extend social protection in a context of high informality.
Keywords: EMPLOYMENT